The Quality of Pre-Hospital Emergency Care for Children with Acute Abdominal Pain: The Prospective Cohort Study Results - Ekaterina A. Romanova; Leyla S. Namazova-Baranova; Elena Yu. Dyakonova; Aleksey Yu. Romanov (Педиатрическая фармакология)
Background. Introduction of laboratory rapid tests into the practice of emergency teams (EMS) and carrying out a simple etiologic point-of-care diagnosis can affect the quality of medical care for children at subsequent stages. Objective. Our aim was to assess the quality of pre-hospital emergency care for children with acute abdominal pain using laboratory rapid tests. Methods. An open prospective comparative randomized study was conducted. Patients who called an emergency team for acute abdominal pain were randomized into two groups. In the study group (n = 243), the proposed model of pre-hospital emergency care with laboratory rapid tests was used. With patients of the control group (n = 242), the emergency teams worked according to the traditional schedule. The quality of medical care for children was assessed taking into account the emergency team specialty. We also carried out the analysis of case management in case of admission to a surgical department. Results. In the study group, the frequency of refusals of hospitalization was 2.5 times lower; the frequency of repeated calls was 75% less; unreasonable admission to a surgical department was 1.5 times less than in the control group (p < 0.05 for all parameters). Non-specialized hospitalization was 5% in the control group no cases in the study group. Conclusion. The use of a laboratory rapid point-of-care diagnosis at the pre-hospital stage helps to improve the quality of care for children with acute abdominal pain.